Postarrest stalling rather than crawling favors CD8+ over CD4+ T-cell migration across the blood-brain barrier under flow in vitro - Rudolph, Henriette (European journal of immunology, 2016)
Although CD8+ T cells have been implied in the pathogenesis of multiple sclerosis (MS), the molecular mechanisms mediating CD8+ T-cell migration across the blood-brain barrier (BBB) into the central nervous system (CNS) are ill defined. Using in vitro live cell imaging, we directly compared the multistep extravasation of activated CD4+ and CD8+ T cells across primary mouse brain microvascular endothelial cells (pMBMECs) as a model for the BBB under physiological flow. Significantly higher numbers of CD8+ than CD4+ T cells arrested on pMBMECs under noninflammatory and inflammatory conditions. While CD4+ T cells polarized and crawled prior to their diapedesis, the majority of CD8+ T cells stalled and readily crossed the pMBMEC monolayer preferentially via a transcellular route. T-cell arrest and crawling were independent of G-protein-coupled receptor signaling. Rather, absence of endothelial ICAM-1 and ICAM-2 abolished increased arrest of CD8+ over CD4+ T cells and abrogated T-cell crawling, leading to the efficient reduction of CD4+, but to a lesser degree of CD8+, T-cell diapedesis across ICAM-1null/ICAM-2−/− pMBMECs. Thus, cellular and molecular mechanisms mediating the multistep extravasation of activated CD8+ T cells across the BBB are distinguishable from those involved for CD4+ T cells.